New insights into the role of cellular senescence and chronic wounds - Yang, Huiqing; Zhang, Xin; Xue, Bo (Frontiers in Endocrinology, 2024)
Chronic or non-healing wounds, such as diabetic foot ulcers (DFUs), venous leg ulcers (VLUs), pressure ulcers (PUs) and wounds in the elderly etc., impose significant biological, social, and financial burdens on patients and their families. Despite ongoing efforts, effective treatments for these wounds remain elusive, costing the United States over US$25 billion annually. The wound healing process is notably slower in the elderly, partly due to cellular senescence, which plays a complex role in wound repair. High glucose levels, reactive oxygen species, and persistent inflammation are key factors that induce cellular senescence, contributing to chronic wound failure. This suggests that cellular senescence may not only drive age-related phenotypes and pathology but also be a key mediator of the decreased capacity for trauma repair. This review analyzes four aspects: the wound healing phase and the cell types involved in wound healing; cellular senescence markers, cytotoxic stressors, and related signaling pathways; the relationship between cellular senescence and typical chronic non-healing wounds; and current and future treatment strategies. In theory, anti-aging therapy may influence the process of chronic wound healing. However, the underlying molecular mechanism is not well understood. This review summarizes the relationship between cellular senescence and chronic wound healing to contribute to a better understanding of the mechanisms of chronic wound healing.